Avant Garde Alleviation -Cancer Immunotherapy - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2019)
Novel cancer therapeutics are superior and prevalent in the current scenario although a subset may not be satisfactorily alleviated or undergo disease relapse with the adoption of conventional chemotherapeutic agents. Cancer cells can comfortably elude immune destruction as interaction of cancer cells with native immune cells within tissue microenvironment is a cogent factor in evasion of cancer cells from pertinent immune surveillance. Thus, cancer immunotherapy can be safely contemplated as an efficacious and contemporary treatment modality for managing various malignant disorders.
Keywords: Immune